2019
DOI: 10.1002/ese3.417
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on evolution in the characteristics of permeability, deformation, and energy of coal containing gas under triaxial cyclic loading‐unloading

Abstract: To further more deeply understand the influence of cyclic loading‐unloading on coal seams during mining and reduce the rock burst and coal and gas outburst disasters and ensure safety during coal mining, triaxial cyclic loading‐unloading tests were performed on coal samples. The permeability recovery rate, residual deformation, and dissipated energy ratio were defined to analyze the evolution in the characteristics of permeability, deformation, and energy observed during the triaxial cyclic loading‐unloading t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 16 publications
(26 reference statements)
0
12
0
Order By: Relevance
“…In fact, the absorption and transformation of energy is the essential cause of rock material failure. [15][16][17][18]. Especially in the dynamic test, the incident energy carried by the incident wave provides the energy source for the failure of rock specimens.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the absorption and transformation of energy is the essential cause of rock material failure. [15][16][17][18]. Especially in the dynamic test, the incident energy carried by the incident wave provides the energy source for the failure of rock specimens.…”
Section: Introductionmentioning
confidence: 99%
“…The failure processes of intact coal samples and coal samples with different prefabricated fractures are dominated by different mechanical mechanisms and show different failure modes macroscopically. Although some researchers have conducted more studies on the mechanics and the permeability characteristics of coal under different cyclic loading and unloading paths, the systematic studies on the constant amplitude cyclic loading and unloading with the pre-peak confining pressure are not enough, and further research studies are necessary.…”
Section: Introductionmentioning
confidence: 89%
“…According to the law of energy conservation, coal and rock are bound to accumulate and dissipate energy during the entire process. 93 Although there are some models of coal and rock based on the energy accumulation and depletion in previous studies, they both neglected the initial accumulate and dissipate energy of coal and rock under the sampling environment before the tests. Therefore, it is suggested that based on fully relying on the continuous improvement advantages of the accuracy for the permeability test of (bedded) coal and rock, the permeability-energy evolution model need to be established considering the initial high in situ stress reduction (see Figure 11), to indirectly quantify the energy accumulation and dissipation of coal and rock in the entire process.…”
Section: Permeability Propertiesmentioning
confidence: 99%
“…However, coal and rock will inevitably be accompanied by a series of evolution processes such as compaction, deformation, damage, and failure under stress‐seepage coupling. According to the law of energy conservation, coal and rock are bound to accumulate and dissipate energy during the entire process 93 . Although there are some models of coal and rock based on the energy accumulation and depletion in previous studies, they both neglected the initial accumulate and dissipate energy of coal and rock under the sampling environment before the tests.…”
Section: Permeability Propertiesmentioning
confidence: 99%